Intraoperative arthroscopy of the TMJ during surgical management of condylar head fractures: A preliminary report - Hirjak, Dusan; Galis, Branislav; Beno, Michal; Machon, Vladimír; Mercuri, Louis G; Neff, Andreas (Journal of cranio-maxillo-facial surgery, 2018)
PURPOSE: The purpose of this preliminary study was to evaluate intraarticular soft tissues of the temporomandibular joint (TMJ) using intraoperative arthroscopy during open reduction and internal fixation (ORIF) of condylar head fractures (CHF). MATERIALS AND METHODS: 26 patients (29 joints) were diagnosed in period of 5 years (2011-2015) with CHF, 5 patients had concomitant mandibular fracture. Fractures were diagnosed on basis of conventional orthopantomogram (OPG) and computed tomography (CT). RESULTS: Intraoperative arthroscopy revealed hyperemia and hypervascularity in all 29 joints, anterior disc dislocation in 26 joints, cartilage erosion in 21 joints and hemorrhagic clots were present in 10 joints. Major hemarthrosis or tear of the posterior band, as often described in MRI, could not be shown in our patients. Data from the study further the understanding of intraarticular pathology of the TMJ after acute trauma in a group with CHF. CONCLUSION: Intraoperative arthroscopy is useful for direct evaluation and accurate diagnosis of the extent of soft tissue damage to TMJ in CHF. Larger and more long-term studies including comparison to MRI findings should be helpful to refine the treatment and postoperative management of patients after CHF.
Keywords: Mandibular Fractures; Intraoperative arthroscopy; Humans; Intraoperative Complications; Adolescent; počítačová rentgenová tomografie; peroperační komplikace; Male; rentgendiagnostika panoramatická; mladiství; vnitřní fixace fraktury; Treatment Outcome; Radiography, Panoramic; lidé středního věku; Mandibular Condyle; Condylar head fracture; lidé; Adult; Fracture Fixation, Internal; výsledek terapie; Tomography, X-Ray Computed; mužské pohlaví; fraktury mandibuly; Retrospective Studies; Female; dospělí; Arthroscopy; Middle Aged; MRI assessment; retrospektivní studie; ženské pohlaví; processus condylaris mandibulae; artroskopie; Soft tissue injury; Disc displacement